Grounding the ways on improving the legislative basis in conducting special operations to cease domestic armed conflict in border areas - Sutyushev, Т. А.; Kryvenko, О. V. (Honor and Law, 2019)
Based upon the analysis of regulations and laws of Ukraine and international agreements as for conducting military and special operations in localization and neutralization of domestic armed conflict in border areas, the ways on improving the legislative basis are determined and grounded.